A comparison of the laryngeal tube with the laryngeal mask airway during spontaneous ventilation in paediatric anaesthesia - Mohamad, Nik Abdullah Nik (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2006)
A randomized prospective study was conducted involving 80 premedicated paediatric patients of ASA 1 and 2, aged between 2 to 10 years. These children were divided into 2 groups, group L T (n=40) received laryngeal tube and group LMA (n=40) received laryngeal mask as airway device. After a standardized inhalational induction of anaesthesia with servoflurane followed by fentany 1.5 pg . kg· 1 , the laryngeal tube or the laryngeal mask airway was inserted and the patients breathed spontaneously throughout the surgery. Anaesthesia was maintained with nitrous oxide, oxygen, and servoflurane. The airway device was removed at the end of surgery when the patient is fully awake. We recorded the speed of insertion and the number of attempts needed to successfully secure the airway. The quality of ventilation as assessed by incidence of oxygen desaturations, frequencies of airway manipulations throughout the surgery and the end-tidal C02 at various time intervals were recorded. The haemodynamic changes such as systolic blood pressure, diastolic blood pressure, mean arterial pressure and heart rate at different time intervals were recorded. We have also recorded the incidence of complications postoperatively. We found that there were significant more time required for successful insertion and more number of attempts for L T group as compared to the LMA group. The number of manipulations of device or patients after first attempt and the recordings of ETC02 recorded at various time intervals was higher with the L T and the difference was significant. However both groups had no statistical difference in episodes of desaturation and haemodynamic parameters during anaesthesia. We found no statistically significant difference in the incidence of complications postoperatively between the two groups. We conclude that during spontaneous ventilation in paediatric patients undergoing general anaesthesia the laryngeal tube-- is not as reliable in providing a satisfactory airway and we consider it is not a suitable alternative to the laryngeal mask airway.